A quick start method for microbial fuel cells. (November 2020) - Lu, Hongbin; Yu, Yin; Xi, Hongbo; Zhou, Yuexi; Wang, Chunrong
Abstract: Microbial fuel cells (MFCs) have great potential to detect toxicity early. Study of toxicity sensors based on MFCs requires a large number of stable MFCs. However, the start-up time of MFCs is generally long, which limits research progress. In this study, a first-stage preculture based on H-type MFCs (first culture) and a second-stage preculture based on multistage MFC reactor series culture (second culture) were used in combination with preculture MFCs. The goal of obtaining an MFC with stable performance in only one day was achieved. The obtained MFC could be stable for 33 h and rapidly regenerated with replacement of the anode substrate. The start-up time was shortened because after the first culture and the secondary culture, the protein content attached to the electrode reached 1.2864 ± 0.0174 mg/cm 2 and 2.22 ± 0.12 mg/cm 2, respectively. Bacteria that generate electricity, such as Geobacter, were effectively enriched. This study may improve the development efficiency of MFC toxicity sensors. Graphical abstract: Image 1 Highlights: First cultures and secondary cultures were used in combination to preculture MFCs. Only one day was needed to obtain an MFC with stable performance. Bacteria that generate electricity, such as Geobacter, were effectively enriched through the preculture.